2010
DOI: 10.1586/era.10.88
|View full text |Cite
|
Sign up to set email alerts
|

Romidepsin: a new therapy for cutaneous T-cell lymphoma and a potential therapy for solid tumors

Abstract: Romidepsin is a histone deacetylase inhibitor (HDI), approved by the US FDA for the treatment of cutaneous T-cell lymphoma (CTCL). Although various mechanisms have been proposed for the activity of HDIs, including induction of genes controlling cell cycle, acetylation of cytoplasmic proteins and direct induction of apoptosis, the mechanism underlying activity of romidepsin and other HDIs in CTCL is not known. Romidepsin induces long-lasting responses. The side-effect profile is similar to that of other HDIs, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(142 citation statements)
references
References 107 publications
0
136
0
1
Order By: Relevance
“…A phase I clinical trial showed JNJ-26481585 to have a much greater plasma half-life of 8.8 hours in patients with advanced solid tumors compared to other HDAC inhibitors, such as vorinostat and romidepsin (49,50), and it shows promise for use in solid tumors either as a single agent or in combination with SOC (35). The dismal plight of those with advanced NSCLC and the observation here that even early-stage tumors are insensitive to current SOCs highlights the need for novel therapeutic or combinatorial options in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I clinical trial showed JNJ-26481585 to have a much greater plasma half-life of 8.8 hours in patients with advanced solid tumors compared to other HDAC inhibitors, such as vorinostat and romidepsin (49,50), and it shows promise for use in solid tumors either as a single agent or in combination with SOC (35). The dismal plight of those with advanced NSCLC and the observation here that even early-stage tumors are insensitive to current SOCs highlights the need for novel therapeutic or combinatorial options in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…SAHA (vorinostat) was approved by the US Food and Drug Administration for the treatment of cutaneous T-cell lymphoma in 2006 [45], as was romidepsin (FK228) in 2009 [57]. Both Mocetinostat (MGCD 0103) and Entinostat (MS-275) are currently undergoing clinical trials for the treatment of various cancer types, including lymphomas and solid tumors [44,58,59].…”
Section: Impact Of Hdac Inhibitors On Cells From Multiple Tumor Speciesmentioning
confidence: 99%
“…This provides the basis of their clinical utility in cancer. Indeed, suberoylanilide hydroxamic acid (SAHA, Vorinostat, Zolinza) and the cyclic peptide, depsipeptide (Romidepsin, Istodax), have been approved by the US FDA, for the treatment of cutaneous T-cell lymphoma [102][103][104][105].…”
Section: Metal-dependent Histone Deacetylases and Histone Deacetylasementioning
confidence: 99%